An investigation of stick-slip oscillation of Mn–Cu damping alloy as a friction material. (June 2020) - Wang, X.C.; Mo, J.L.; Ouyang, H.; Huang, B.; Lu, X.D.; Zhou, Z.R.
Abstract: The capability of Mn–Cu damping alloy in suppressing stick-slip oscillation when used as the friction pair material is investigated through the experimental method and the forged steel, cast iron, Al alloy and Mn–Cu alloy are chosen for the comparative study. The results show that the Mn–Cu damping alloy and Al alloy have a great potential in suppressing stick-slip oscillation as compared with others. The results also reveal the varying wear behaviours and the relationship between the wear state and the stick-slip oscillation. They indicate that the wear debris on the contact interface make a noticeable contribution to reduce stick-slip oscillation. In addition, the high damping capacity of the Mn–Cu damping alloy may also help to suppress the stick-slip oscillation. Highlights: Five kinds of discs are tested to find out their stick-slip vibration behaviour. The Mn–Cu damping alloy shows a strong ability to suppress stick-slip vibration. The Mn–Cu damping alloy disc undergoes severe wear and produces many wear debris. The wear debris and high damping capacity are believed to help reduce stick-slip vibration.